IITA Annual Report 2004 - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2005)
The International Institute of Tropical Agriculture (IITA) is more than a collection of research stations and scientific initiatives. IITA consists of dedicated people who provide technical skills and original ideas to improve the lives of people in sub-Saharan Africa. IITA works in close partnership with a wide range of expert collaborators, including farmers, research and extension staff of national programs, governments, regional organizations, agri-business, private foundations, nongovernmental organizations, advanced research institutions, and a host of others both within and outside Africa. Our cooperative efforts result in the development of innovations which contribute to food security. Such novel technologies include development of integrated pest management options, ways for farmers to access crucial market information, increased nutritional value of food crops, ensuring the economic and environmental sustainability of varied cropping systems or the supply of key information to policy makers. IITA is optimistic that the agricultural sector can go beyond provision of food security to serve as an engine for economic development by creating wealth for farm families, villages, districts, countries, and regions in sub-Saharan Africa. Africa is a continent rich in natural and human resources. Furthermore, many IITA technologies have contributed to increasing the quantity and quality of agricultural produce across the continent. However, since 1990, while the food available per person has increased in Latin America (+30%) and Asia (+20%), Africa has experienced a 3% decline (InterAcademy Council, 2004). Notwithstanding such alarming statistics, IITA has observed the potential provided by entrepreneurs who are using agricultural commodities to drive a chain resulting in increased profits for men and women from the farm to the consumer. Now is a critical time for sub-Saharan Africa. The New Partnership for Africa’s Development (NEPAD) has shown the commitment of Africa’s leaders to “business unusual” across the continent. IITA is both honored and excited by the role that it has been asked to play in NEPAD’s pan-African cassava initiative. IITA has also been invited to work with NEPAD on the African Union’s Comprehensive African Agricultural Development Programme, as well as contribute to the important activities of other subregional trade and research organizations. IITA and its collaborators are committed to the UN’s Millennium Development Goals, and the significant benefit to poor people which will result. The experience and capacity of IITA permit us to play a determinant role in Africa’s ongoing emphasis on agriculture as a driver of economic development. The Research for Development Council is a leadership group (composed of elected scientists and Directors) which aims to ensure that IITA’s strategic capability is harmonized to the challenges and opportunities on the horizon. IITA will play an active role to maximize the continent’s remarkable agricultural potential in order to catalyze economic development. L’institut international d’agriculture tropicale, l’IITA est plus qu’un rassemblement de stations de recherches et d’initiatives scientifiques. L’IITA se compose de personnes dédiées qui fournissent les compétences techniques et les idées originales pour améliorer le niveau de vie des gens en Afrique sub-saharienne. L’IITA travaille en partenariat avec une grande gamme de collaborateurs experts y compris des cultivateurs, des chercheurs et le personnel de vulgarisation de programmes nationaux, des gouvernements, des agro-entrepreneures, des organisations nongouvernementales, des institutions à recherches avancées et bien d’autres en Afrique et ailleurs. Nos efforts de coopération se traduisent dans le développement des innovations qui contribuent à la sécurité alimentaire. De telles nouvelles technologies incluent le développement des options intégrées pour le contrôle des pestes, les moyens par lesquels les cultivateurs peuvent avoir les renseignements cruciaux à propos du marché, l’amélioration de valeur nutritive des cultures, la durabilité économique et de l’environnement de divers systèmes culturaux, ou la provision des informations clés aux décideurs de politiques. L’IITA est optimiste que le secteur agricole peut non seulement assurer la provision des aliments mais aussi servir comme moteur pour le développement économique à travers la création de richesses pour les familles de cultivateurs, les villages, les arrondissements, les pays et les régions en Afrique sub-saharienne. L’Afrique est un continent riche en ressources naturelles et humaines. De plus, beaucoup de technologies de l’IITA ont contribué à la croissance de la quantité et la qualité des produits agricoles à travers le continent. Pourtant, depuis 1990, alors que la nourriture disponible par personne a augmenté en Amérique latine (+30%) et en Asie (+20%), l’Afrique a connu un déclin de 3% (InterAcademy council, 2004). Malgré ces statistiques alarmantes, l’IITA a remarqué le potentiel de création par les entrepreneurs qui se servent de produits agricoles pour générer une filière qui résulte en profits croissants pour les hommes et les femmes, du producteur au consommateur. Nous traversons une période critique pour l’Afrique subsaharienne. Le Nouveau partenariat pour le développement de l’Afrique (NEPAD) a montré l’engagement des dirigeants africains à une ‘affaire inhabituelle’ à travers le continent. L’IITA est non seulement honoré mais aussi excité par le rôle qui lui a été demandé de jouer dans l’initiative pan-Africaine du manioc du NEPAD. L’IITA a été aussi invité pour travailler avec le NEPAD en ce qui concerne le Programme détaillé pour le développement de l‘agriculture africaine de l‘Union africaine, ainsi qu’à contribuer aux activités importantes d‘autres organisations sous-régionales de commerce et de recherche. L’IITA et ses collaborateurs sont dévoués aux buts de développement des Nations-Unies pour le millenium, et les bénéfices importants qui en sortiront pour les gens pauvres. L’expérience et la capacité de l’IITA nous permettent de jouer un rôle déterminant dans l’accent que l’Afrique mets actuellement sur l’agriculture en tant que stimulant du développement économique. Le Conseil de la recherche pour le développement est un groupe de direction (composé de scientifiques et administrateurs) qui a comme objectif de s’assurer de la capacité stratégique de l’IITA à s’harmoniser avec les défis et les opportunités qui se pointent à l’horizon. L’IITA continuera de jouer un rôle actif pour maximiser le potentiel agricole remarquable du continent en vue de stimuler le développement économique.